Czwórka i Eska z wizją, czyli o tym, jak radio łączy się z telewizją - Baran, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The era of digitization has led to a shift in radio from a strictly audial character toward audio-visual experiences. This article aims to characterize the transmedia actions performed by the Radio Four Polish Station and Radio Eska. In the cases described, a convergence has been carried out on the technological level which allows for information to be transmitted more succinctly. Yet, it is still characterized by its ephemeral and linear nature, which remains a unique feature of traditional media. The article presupposes that the television medium is not flexible and autonomic enough towards time and space to dominate radio broadcasting.